2015
DOI: 10.1007/s10096-015-2448-0
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in host genes encoding NOSII, C-reactive protein, and adhesion molecules thrombospondin and E-selectin are risk factors for Plasmodium falciparum malaria in India

Abstract: Cytoadherence of Plasmodium falciparum-infected red blood cells (RBCs) in host microvasculature and complex regulation of the immune response are important contributors to the clinical outcome of disease. We tested the association of 23 single nucleotide polymorphisms (SNPs) and a microsatellite repeat in adhesion molecule genes THBS1 and ESEL, and immune regulatory molecule genes NOSII, CRP, and MBL2 with falciparum malaria in populations residing in a malaria-endemic and a non-endemic region of India. The TH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
(81 reference statements)
1
6
0
Order By: Relevance
“…The utility of an India-specific baseline variability has been demonstrated during pre-next-generation sequencing (NGS) days-in infectious diseases (e.g., malaria, HIV), pharmacogenomics studies, disease associations, and identification of at-risk populations for various neurological, cutaneous, and high-altitude adaptation-related disorders (Aggarwal et al, 2010(Aggarwal et al, , 2015Bhattacharjee et al, 2008;Biswas et al, 2007Biswas et al, , 2010Chaki et al, 2011;Giri et al, 2014;Grover et al, 2010;Gupta et al, 2007;P. Jha et al, 2012;Kanchan et al, 2015;Kumar et al, 2009;Sinha, Arya, Agarwal, & Habib, 2009;Sinha et al, 2008;Talwar et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The utility of an India-specific baseline variability has been demonstrated during pre-next-generation sequencing (NGS) days-in infectious diseases (e.g., malaria, HIV), pharmacogenomics studies, disease associations, and identification of at-risk populations for various neurological, cutaneous, and high-altitude adaptation-related disorders (Aggarwal et al, 2010(Aggarwal et al, , 2015Bhattacharjee et al, 2008;Biswas et al, 2007Biswas et al, , 2010Chaki et al, 2011;Giri et al, 2014;Grover et al, 2010;Gupta et al, 2007;P. Jha et al, 2012;Kanchan et al, 2015;Kumar et al, 2009;Sinha, Arya, Agarwal, & Habib, 2009;Sinha et al, 2008;Talwar et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, mitochondrial and Y chromosome haplogroup‐based studies have also helped in the characterization of the gene pool of diverse Indian populations (Bamshad et al, 2001; Borkar, Ahmad, Khan, & Agrawal, 2011; Kivisild et al, 2003; Majumder et al, 1999; Thanseem et al, 2006). The utility of an India‐specific baseline variability has been demonstrated during pre‐next‐generation sequencing (NGS) days—in infectious diseases (e.g., malaria, HIV), pharmacogenomics studies, disease associations, and identification of at‐risk populations for various neurological, cutaneous, and high‐altitude adaptation‐related disorders (Aggarwal et al, 2010, 2015; Bhattacharjee et al, 2008; Biswas et al, 2007, 2010; Chaki et al, 2011; Giri et al, 2014; Grover et al, 2010; Gupta et al, 2007; P. Jha et al, 2012; Kanchan et al, 2015; Kumar et al, 2009; Sinha, Arya, Agarwal, & Habib, 2009; Sinha et al, 2008; Talwar et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In order to identify the risk of individual developing malaria and to predict the outcome, we analysed multiple alterations in ABCB1 and related its impact on the disease. Genetic variants, their functional relevance to Pf as well as to other infectious diseases [51] can provide important information on the aetiology of the disease. Previously described protective alleles against malaria relate to genes that are involved with the host immune response such as cytokines, endothelial receptor, complement regulatory gene, HLA gene and RBC structure [5054].…”
Section: Discussionmentioning
confidence: 99%
“…They observed that these resistance genes even though present at high frequency among all 3 ethnic groups, show interethnic heterogeneities towards the susceptibility to malaria [62]. Similarly, some of the SNPs show a high correlation to malaria whereas, the same SNP shows no association when the study is carried out either in other population, geographical area, endemic/non-endemic regions, ethnic groups or tissue samples [51, 57, 63]. There are SNPs reported which even show the inverse correlation with respect to sex and age [64].…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the IGV consortium have led to the identification of specific markers and better understanding of genotype-phenotype correlations in Indian sub-populations. The phenotypically distinct outcomes of sub-population specific genotypes could be shown in susceptibility or resistance towards Plasmodium falciparum [2327], risk of contracting glaucoma [28], homocysteine levels [29], and risk of developing high-altitude pulmonary edema [30, 31], among other examples. Further, case-control studies in ethnically matched groups as defined by IGV consortium allowed identification of Indian-specific susceptibility markers in genes causing Parkinson’s disease, Wilson disease, and albinism [3235].…”
Section: Introductionmentioning
confidence: 99%